Evaluating YouTube Videos With Prophylactic Mastectomy Content in Terms of Their Quality and Reliability - Tansu Altintas; Mehlika Bilgi Kirmaci (The Breast Journal)
Conclusion: In our study, we found that the videos uploaded by doctors were of good quality, the videos uploaded by health channels were of medium quality, and the videos uploaded by patients were of poor quality and misleading. The videos with health contents should be evaluated by the relevant specialists, and only useful videos should be broadcast.